2014
DOI: 10.1007/s11240-014-0598-x
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced resistance to Botrytis cinerea in genetically-modified Vitis vinifera L. plants over-expressing the grapevine stilbene synthase gene

Abstract: Grapevine (Vitis vinifera L.) was genetically modified with a construct containing a cDNA insert encoding the stilbene synthase gene (Vst1) from grapevine, under the control of the cauliflower mosaic virus 35S promoter in order to test the potential of over-production of resveratrol to protect plants from fungal attack. Southern blot hybridization and quantitative real-time PCR analysis demonstrated the presence and integration of one copy of exogenous DNA sequences in two grapevine-modified lines. Relative ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Stilbenoids show ROS scavenging activity acting as a powerful defense system against biotic stresses (e.g., powdery mildew, downy mildew; Dabauza et al, 2015 ; Houillé et al, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Stilbenoids show ROS scavenging activity acting as a powerful defense system against biotic stresses (e.g., powdery mildew, downy mildew; Dabauza et al, 2015 ; Houillé et al, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…The authors showed variations in modulation of genes involved in the phenylpropanoid pathway (mainly stilbene and flavonoid genes), suggesting a resveratrol-mediated way to enhance water stress resilience in a tolerant rootstock genotype. Stilbenoids (resveratrol and viniferin in particular) have reactive oxygen species (ROS) scavenging activity and act as a powerful defense system against biotic stresses (e.g., powdery mildew, downy mildew; Dabauza et al, 2015 ; Houillé et al, 2015 ). Furthermore, it is well-known that Vitis vinifera represents the best nutritional source of stilbenoid compounds with valuable effects on human health; these compounds have numerous pharmacological activities including anti-fungal, anti-inflammatory and anti-tumor effects (Bai et al, 2010 ; Zhang et al, 2010 ; Houillé et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…The npt II gene confers resistance to aminoglycoside antibiotics such as kanamycin and paromomycin. In most studies on transformation of grapevine SCC kanamycin has been the most frequently used selection agent although at very diverse concentrations from 10 to 100 mg L −1 , probably depending on the Vitis genotype. In the present study we found that Monastrell cells are almost insensitive to kanamycin and the selection was carried out with paromomycin, since this antibiotic had been previously used by other authors to select transformed grapevine tissues .…”
Section: Discussionmentioning
confidence: 99%
“…In vitro infection tests with Botrytis cinerea were carried out on grapevine micro cuttings transformed with the V. vinifera Vst1 gene under the control of a promoter inducible by fungal infection (PR10 promoter isolated from alfalfa); the results obtained confirmed an enhanced resistance against the pathogen in the transgenic lines that exhibited the highest resveratrol synthesis level [ 51 ]. In another study, the expression of the Vst1 gene under the cauliflower mosaic virus 35S promoter resulted in smaller botrytis necrotic lesion size in transgenic grapevine in comparison with control plants, demonstrating the existence of a positive correlation among resveratrol content and resistance to Botrytis cinerea [ 52 ]. In transgenic Arabidopsis plants, the expression of the Vitis pseudoreticulata STS gene ( VpSTS ), encoding a novel stilbene synthase, led to greater resistance to powdery mildew, since its expression seemed to be stimulated by SA, as happens with the expression of its homologous allele from susceptible Vitis vinifera [ 56 ].…”
Section: Genetic Engineering For the Expression Of Candidate Genesmentioning
confidence: 99%